Highly Functionalized and Potent Antiviral Cyclopentane Derivatives Formed by a Tandem Process Consisting of Organometallic, Transition‐Metal‐Catalyzed, and Radical Reaction Steps. Issue 33 (10th July 2014) - Jagtap, Pratap R.; Ford, Leigh; Deister, Elmar; Pohl, Radek; Císařová, Ivana; Hodek, Jan; Weber, Jan; Mackman, Richard; Bahador, Gina; Jahn, Ullrich
Abstract A simple modular tandem approach to multiply substituted cyclopentane derivatives is reported, which succeeds by joining organometallic addition, conjugate addition, radical cyclization, and oxygenation steps. The key steps enabling this tandem process are the thus far rarely used isomerization of allylic alkoxides to enolates and single‐electron transfer to merge the organometallic step with the radical and oxygenation chemistry. This controlled lineup of multiple electronically contrasting reactive intermediates provides versatile access to highly functionalized cyclopentane derivatives from very simple and readily available commodity precursors. The antiviral activity of the synthesized compounds was screened and a number of compounds showed potent activity against hepatitis C and dengue viruses.